Silk-Elastin-like Polymers for Acute Intraparenchymal Treatment of the Traumatically Injured Spinal Cord: A First Systematic Experimental Approach - Pau González; Carlos González-Fernández; Alfredo Maqueda; Virginia Pérez; Sara Escalera-Anzola; Ángel Rodríguez de Lope; Francisco Javier Arias; Alessandra Girotti; Francisco Javier Rodríguez (Pharmaceutics, 2022)
Despite the promising potential of hydrogel-based therapeutic approaches for spinal cord injury (SCI), the need for new biomaterials to design effective strategies for SCI treatment and the outstanding properties of silk-elastin-like polymers (SELP), the potential use of SELPs in SCI is currently unknown. In this context, we assessed the effects elicited by the in vivo acute intraparenchymal injection of an SELP named (EIS)2-RGD6 in a clinically relevant model of SCI. After optimization of the injection system, the distribution, structure, biodegradability, and cell infiltration capacity of (EIS)2-RGD6 were assessed. Finally, the effects exerted by the (EIS)2-RGD6 injection—in terms of motor function, myelin preservation, astroglial and microglia/macrophage reactivity, and fibrosis—were evaluated. We found that (EIS)2-RGD6 can be acutely injected in the lesioned spinal cord without inducing further damage, showing a widespread distribution covering all lesioned areas with a single injection and facilitating the formation of a slow-degrading porous scaffold at the lesion site that allows for the infiltration and/or proliferation of endogenous cells with no signs of collapse and without inducing further microglial and astroglial reactivity, as well as even reducing SCI-associated fibrosis. Altogether, these observations suggest that (EIS)2-RGD6—and, by extension, SELPs—could be promising polymers for the design of therapeutic strategies for SCI treatment.